1982
DOI: 10.6028/nbs.ir.81-2448
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air mass and integration methods on results for optical property measurements of solar cover plate and absorber materials

Abstract: This study was undertaken to compare methods of calculating the transmittance of cover plate materials and the reflectance of absorber materials. The study was limited to evaluation of factors which influence the results with method A of ASTM E 424, Optical data were obtained for both aged and unaged test specimens using an integrating sphere spectrophotometer. The data were integrated using: (1) the weighted and selected ordinate methods in ASTM E 424, Method A, at air mass 2.0, and (2) the selected ordinate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1983
1983
1984
1984

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…• -and accelerated weathering [62,63]; determination of cover plate pr per::*.-69 including stability, warpage, and mechanical response [62]; measurement of optical properties [64]; and determination of procedures for assessing hail impact on the durability of cover plate materials [65] In the first study [62], researchers identified field problems, determined performance requirements for and properties of cover plate materials, and identified degradation factors.…”
Section: N3s Conducted Research In Several Areasmentioning
confidence: 99%
See 2 more Smart Citations
“…• -and accelerated weathering [62,63]; determination of cover plate pr per::*.-69 including stability, warpage, and mechanical response [62]; measurement of optical properties [64]; and determination of procedures for assessing hail impact on the durability of cover plate materials [65] In the first study [62], researchers identified field problems, determined performance requirements for and properties of cover plate materials, and identified degradation factors.…”
Section: N3s Conducted Research In Several Areasmentioning
confidence: 99%
“…Most solar collectors, however, are exposed to more hours of radiation that approximates air mass 1.5. As a result, Roberts, Masters, and Clark [64] assessed the effect of varying air mass value upon the transmittance and reflectance values of typical materials. They determined that the three values of air mass studied, 1.0, 1.5, and 2.0, could vary the obtained transmittance values by as much as 4 percent.…”
Section: N3s Conducted Research In Several Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…The NBS subsequently conducted a study [5] in which the aforementioned transmittance data were analyzed to determine the influence of air mass and integration technique on Method A of ASTM Standard E424 [4] for measuring solar energy transmittance. As mentioned above.…”
Section: Parametric Study Of Optical Propertiesmentioning
confidence: 99%
“…In the above mentioned parametric study of cover plates (section 2.1.3) [5], NBS also analyzed laboratory test data on the performance of absorber materials. The purpose of the study was to assess the effect of several variables on an ASTM standard method for measuring the reflectance of absorber materials (Method A of ASTM E424).…”
Section: Parametric Study Of Optical Propertiesmentioning
confidence: 99%